Scalable electrochromic nanopixels using plasmonics - Peng, Jialong (Sci Adv, 2019)
Plasmonic metasurfaces are a promising route for flat panel display applications due to their full color gamut and high spatial resolution. However, this plasmonic coloration cannot be readily tuned and requires expensive lithographic techniques. Here, we present scalable electrically driven color-changing metasurfaces constructed using a bottom-up solution process that controls the crucial plasmonic gaps and fills them with an active medium. Electrochromic nanoparticles are coated onto a metallic mirror, providing the smallest-area active plasmonic pixels to date. These nanopixels show strong scattering colors and are electrically tunable across >100-nm wavelength ranges. Their bistable behavior (with persistence times exceeding hundreds of seconds) and ultralow energy consumption (9 fJ per pixel) offer vivid, uniform, nonfading color that can be tuned at high refresh rates (>50 Hz) and optical contrast (>50%). These dynamics scale from the single nanoparticle level to multicentimeter scale films in subwavelength thickness devices, which are a hundredfold thinner than current displays.